Pengembangan Sistem Informasi Manajemen Kegiatan Masjid Berbasis Website pada Masjid Al Hikmah - Budimansyah Purba, Arif; Ahmad Mubarok; Jajang Mulyana; Wawan Kusdiawan (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
This research aims to develop a web-based Mosque Management Information System (SIMM) to manage the administrative and operational activities of mosques. The method used in this research is the Systems Development Life Cycle (SDLC) Waterfall model. The SDLC phases include Project Planning Phase, Analysis Phase, Design Phase, Implementation Phase, and Support Phase. This research was conducted at Al Hikmah Mosque, located in Grand Samara Residence, Dusun Kopo, Klari Village, Karawang District. Data and information were collected through surveys and interviews with mosque administrators. The results show that the developed web-based SIMM can improve efficiency in data management, enhance coordination among stakeholders, and increase transparency in financial management. The system was well received by mosque administrators and is expected to improve the overall quality of mosque management. Additionally, this SIMM is expected to provide better services to the congregation and increase the accountability of mosque administrators.